Utility and construct validity of an ethical dilemmas scale in management education - Loo, Robert (Journal of business ethics, 1996)
Business ethics has gained much attention over the past decade in both work and educational settings. This study used a version of Lysonski and Gaidis' (1991) ethical vignettes to examine by gender the ethical views of 165 Canadian undergraduate management students, to examine the psychometric properties and construct validity of the instrument, and to determine if the instrument is a useful tool for introducing undergraduates to the topic of ethics in management practice. Results showed that while the instrument is a useful teaching tool, it has psychometric and validity inadequacies that need to be corrected.